(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Propionibacterium acnes virulence factors can be divided into chromosomal, plasmid and bacteriophages encoded virulence factors. Many of the Propionibacterium acnes virulence factors, are camp5, gehA, tly, sialidases, neuraminidases, endoglycoceramidases, lipases, and hemolysins genes are clustered in certain areas of the chromosome. A total of 200 clinical acne samples were collected during this study which obtained from patient Suffering from acne vulgaris who to the out-patient clinics and delivery dermatology unite of acne, in hospitals of Babylon Province: AL-Hashmeia general Hospital and Marjan hospital, during the period from April to November 2019. Out of 200 specimens 14 (7.7%)were detected by culture and vitek2 compact9 (64.3%)of them were confirmed by PCR using target gene of Propionibacterium acnes PCR was conducted to determine the some virulence genes of the isolates by using primers nan, tly and dsA gene. The PCR amplification products were visualized by electrophoresis on 1% agarose gels for 35min at 70v. The sizes of the amplicons were determined by comparison to the 200 bp allelic ladder. Among isolates studies it was found that nan gene present in 6/9(66.7%). isolates, dsA gene it was found in only 3isolates (33.4%) while tly gene it was found in all isolates(100%) .